Aging of Pyrotechnic Compounds with Infrared and Thermal Analysis - Gouranlou, Farideh (Asian Journal of Chemistry, 2010)
Pyrotechnics are compounds that have low weight but have high internal energy. In this article, it is decided to understand the age of samples of pyrotechnic that have maleonitrile. The infrared and thermal analysis were performed for identification of samples differences.